On the influence factors of audio-visual comfort of mountain landscape based on field surve - Liu, Fangfang; Kang, Jian; Meng, Qi (Journal of Environmental Engineering and Landscape Management, 2020)
This study is aimed to investigate factors that can affect the audio-visual comfort of tourists with a mountainous landscape. The results reveal that the audio-visual comfort of tourists is positively correlated with the percentage of tourists engaged in a dynamic state. In contrast, the audio-visual comfort has strong negative correlations with density, sound pressure level and sound characters including fluctuation and loudness. Overall, respondents in the mountain area find the audio-visual level most comfortable when the ratio of visitors in dynamic states is greater than 33%, the fluctuation of sound is within 0.08 vacil, the loudness of sound is less than 46 sone, the population density is less than 0.822 person/m2, and the sound pressure level is less than 82 dB. Compared with urban areas, a 24 dB increase in the sound pressure level threshold is observed for a positive evaluation of audio-visual comfort in the mountain area.